Do Preservice Teachers’ Pedagogical Competence and English Skills Correlate to Their Willingness to be Teachers? - Eko Sasmito; Armeria Wijaya (Acitya: Journal of Teaching and Education, 2022)
English teacher is one of the main factors to students to master English. Their competencies will lead them into professional teachers. Aiming to know the correlation between pedagogical and English skills of the pre-service teacher to their willingness to be teachers, this research uses an explanatory correlation design. Documents of pedagogical competence and English skills score and questionnaire are the instruments of the research. The result of the analysis shows that there is a significant correlation between pre-service pedagogical competence and their willingness to be teachers. Meanwhile, there is no correlation between pre-service English skills and their willingness to be. Then, there is no correlation between pre-service pedagogical competence and English skill together with their willingness to be teachers. However, from the findings, it can be concluded that pre-service teachers’ pedagogical competence affects their willingness to be teachers, that pre-service teacher is suggested to master teacher competencies to increase their willingness to be teacher especially pedagogical competence.